Phenylephrine Decreases Vascular Tension in Goat Arteries in Specific Circumstances. - Renu R Raj; Sathya Subramani (PLoS ONE, 2016)
Phenylephrine (PE) causes vasoconstriction through alpha adrenergic receptors. PE-induced vasodilatation has also been reported earlier in pre-constricted vessels. Here we demonstrate in spiral strips of goat arteries that addition of PE can decrease tone even from base-line levels (i.e. not pre-constricted) and show that this process requires nitric oxide (NO) and alpha adrenergic stimulation, but is cGMP-independent. Under control conditions, PE caused vasoconstriction, but under conditions where NO levels are higher, as with L-Arginine or sodium nitroprusside, PE decreased vessel tension. L-Arginine/PE combination was not able to decrease tension when alpha adrenoceptors were blocked with Phentolamine or endothelial nitric oxide synthase (eNOS) was blocked with Nω-Nitro-L-arginine (L-NNA). Propranolol, a beta blocker, was unable to prevent the reduction in tension by the L-Arginine/PE combination. Adrenaline and noradrenaline (and not isoproterenol) also reduced vessel tension in the presence of L-Arginine. Even when NO levels were not enhanced, relieving NO from having to stimulate the enzyme soluble guanylyl cyclase (sGC) (either by using sGC blockers, namely ODQ or methylene blue, or by enhancing cGMP levels (with sildenafil) which by negative feedback probably inhibits sGC) led to PE-induced reduction of vascular tension. PMA-phorbol myristate acetate-an agonist which stimulates Protein Kinase C was able to prevent the ability of PE to reduce vascular tension in a high NO environment. Our conclusion is that PE reduces vascular tension through alpha adrenoceptors if there is excess NO availability to activate a putative pathway. Though the reduction of vessel tone by PE is dependent on NO, it is independent of cGMP. Prior treatment with PMA or PE itself can prevent further PE-induced reduction of tension in a high NO environment. The results here suggest, counter-intuitively, that alpha blockers may be of help in the treatment of septic shock where nitric oxide levels are high.